Identification of a novel locus C2 controlling canary yellow flesh color in watermelons - Park, Girim; Shahwar, Durre; Jang, Gaeun; Shin, Jagyeong; Kwon, Gibeom; Kim, Younjae; Hong, Chang Oh; Jin, Bingkui; Kim, Hoytaek; Lee, Oakjin; Park, Younghoon (Frontiers in Genetics, 2023)
This is a provisional file, not the final typeset article the marker (M7) derived from a non-synonymous SNP of the pentatricopeptide repeat gene (ClPPR, Cla97C02G039880). Additionally, 27 watermelon inbred lines of ICY, CY and red flesh were evaluated using previously reported Cllcyb (C locus)-based markers and our C2 locus-linked ClPPRbased marker (M7). As a result, dominant alleles at C2 locus were required to produce CY, in addition to dominant alleles at C locus, while a recessive homozygous genotype at the C locus gave the red flesh irrespective of the genotype at the C2 locus. Using a ClPPR-based CAPS developed in this study and Cllcyb-based markers, watermelon cultivars with CY, ICY, and red flesh could be successfully discerned, implying that combined use of these markers will be efficient for marker-assisted selection (MAS) of flesh color in watermelon breeding.